Detection rate of fluorine-18 prostate-specific membrane antigen-1007 PET/CT for prostate cancer in primary staging and biochemical recurrence with different serum PSA levels: A systematic review and meta-analysis - Liu, Xue; Jiang, Tao; Gao, CaiLiang; Liu, HuiTing; Sun, Yu; Zou, Qiao; Tang, Rui; Zeng, WenBing (Frontiers in Oncology, 2022)
Background We performed a systematic review and meta-analysis to evaluate the detection rate (DR) of fluoro-prostate-specific membrane antigen (18F-PSMA-1007) PET/CT in patients with different serum prostate-specific antigen (PSA) levels in the setting of primary staging of prostate cancer (PCa) or biochemically recurring PCa. Methods A comprehensive electronic literature search of the PubMed, Embase, and Cochrane Library databases was conducted in accordance with the PRISMA statement. This study was registered in the PROSPERO database (registration number: CRD42022331595). We calculated the DR of 18F-PSMA-1007 PET/CT in PCa. Results The final analysis included 15 studies that described 1,022 patients and 2,034 lesions with 18F-PSMA-1007 PET/CT in PCa. The DR of 18F-PSMA-1007 PET/CT in patients with PCa in primary staging ranged from 90% to 100%, with a pooled estimate of 94% (95% CI: 92%–96%). The DR of 18F-PSMA-1007 PET/CT in patients with PCa in BCR ranged from 47% to 100%, with a pooled estimate of 86% (95% CI: 76%–95%). The DRs of PSA levels >2.0, 1.1–2.0, 0.51–1.0, and ≤0.5 ng/ml detected by 18F-PSMA-1007 PET/CT in a patient-based analysis were 97% (95% CI: 93%–99%), 95% (95% CI: 88%–99%), 79% (95% CI: 68%–88%), and 68% (95% CI: 58%–78%), respectively. Conclusion This meta-analysis concluded that 18F-PSMA-1007 PET/CT had a high application value for prostate cancer, including primary tumors and biochemical recurrence. The DR of 18F-PSMA-1007 PET/CT was slightly higher in primary prostate tumors than in biochemical recurrence. Systematic Review Registration https://www.crd.york.ac.uk/prospero/, identifier CRD42022331595.